1993
DOI: 10.1159/000139860
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Carcinogenicity Study with Sennosides in the Rat: Emphasis on Gastro-lntestinal Alterations

Abstract: A carcinogenicity study was conducted by administering a purified senna extract via the drinking water to Sprague-Daw-ley rats of each sex for 2 years. The daily doses received were 0, 5, 15 and 25 mg/kg. Histopathological examination was restricted to tissues from the gastrointestinal tract, liver, kidneys, adrenals and from tissues with any observed abnormalities or masses. A laxative effect was observed in high-dose females, and in mid- and high-dose males. No significant differences in survival were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 14 publications
2
20
0
Order By: Relevance
“…There is no evi dence that in the rodent model tumors would develop based on these changes. In the case of sennosides, this is also supported by the find ings of Lyden-Sokolowski et al [20] who found no cancerogenic potential of a senna extract given to rats over a period of 2 years.…”
Section: Discussionsupporting
confidence: 53%
“…There is no evi dence that in the rodent model tumors would develop based on these changes. In the case of sennosides, this is also supported by the find ings of Lyden-Sokolowski et al [20] who found no cancerogenic potential of a senna extract given to rats over a period of 2 years.…”
Section: Discussionsupporting
confidence: 53%
“…Increased cell proliferation in the rat intestine has also been reported for sennoside A and other active laxative compounds like danthron, bisacodyl and magnesium sulfate (Toyoda et al 1994). However, increased cell proliferation of the large intestine was not observed in other studies on rats following long-term exposure to a senna extract or pure sennosides (Mengs 1988;Geboes et al 1993;Lyden-Sokolowski et al 1993).…”
Section: Discussionmentioning
confidence: 84%
“…These findings led to an increase in concern about the safety of anthranoid laxatives since it has been speculated that the chronic use might cause colorectal cancer in humans (Westendorf et al 1990;Siegers 1992;Westendorf 1993). It is important to note that senna has never been shown to increase the incidence of colorectal cancer in nonclinical or clinical studies (Kune 1993;Lyden-Sokolowski et al 1993;Nusko et al 1993;Loew et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs and preparations which vary in a wide range in respect to their HA content become comparable with the risk index. The knowl edge of the potential aloe-emodin and emodin contents in senna preparations administered for genotoxicity [5], cancerogenicity [11], and pharmacokinetic studies [ 12] is of high impor tance for the interpretation of their results.…”
Section: Discussionmentioning
confidence: 99%